Neutrophil extracellular traps stimulate proinflammatory responses in human airway epithelial cells - Sabbione, Florencia (2017)
Tissue injury leads to the release of uric acid (UA). At high local concentrations, UA can form monosodium urate crystals (MSU). MSU and UA stimulate neutrophils to release extracellular traps (NET). Here, we investigated whether these NET could be involved in the development of inflammation by stimulating cytokine release by airway epithelial cells. We found that NET significantly increased the secretion of CXCL8/IL-8 and IL-6 by alveolar and bronchial epithelial cells. These effects were not observed when NETosis was inhibited by Diphenyleneiodonium, elastase inhibitor, or Cl-amidine. Similar findings were made with NET induced by cigarette smoke extract, suggesting that NET proinflammatory capacity is independent of the inducing stimulus. Furthermore, NET affected neither the viability and morphology of epithelial cells nor the barrier integrity of polarized cells. The epithelial stimulatory capacity of NET was not affected by degradation of DNA with micrococcal nuclease, treatment with heparin, or inhibition of the elastase immobilized to DNA, but it was significantly reduced by pretreatment with an anti-HMGB-1 blocking antibody. Altogether, our findings indicate that NET exert direct proinflammatory effects on airway epithelial cells that might contribute in vivo to the further recruitment of neutrophils and the perpetuation of inflammation upon lung tissue damage.